Turfgrass Disease Management - Monica L. Elliott; Philip F. Harmon (EDIS, 2011)
Turfgrass diseases are underappreciated because the biological organisms (plant pathogens) causing the problems are rarely observed. Fortunately, grasses maintained using proper cultural practices (water, mowing, and fertility) are not as likely to become diseased or be as severely damaged as grasses that do not receive proper care. This 11-page revised fact sheet discusses turfgrass diseases, their causal agents, diagnosis, and management. Written by M. L. Elliott and P. F. Harmon and published by the UF Department of Plant Pathology, February 2011.